The Use of Computer and Developmental Educational Technologies in the Development of Phonetic Competence of Students in the English Language - Uktamovich, Marufov Elyor (European Journal of Life Safety and Stability (2660-9630), 2023)
In this article, computer and developmental educational technologies in the development of phonetic competence of students in English their use means of teaching correct pronunciation various programs and autentic video courses are considered.